- #1
RVP91
- 50
- 0
By conditioning on the value of X1, and then thinking of future generations as a particular
generation of the separate branching processes spawned by these children, show that Fn(s),
defined by Fn(s) = E(s^Xn), satisfies
Fn(s) = F(Fn−1(s)) ∀n ≥ 2.
I need to prove the above result and have somewhat of an idea how to but I can't get the end result.
Here is my working thus far.
Fn(s) = E(s^Xn) = E(s^X1 + X2 +...+Xn) = E(s^j+X2+..+Xn) = s^j(E(s^Xn-1)
Then E(s^Xn | X1=j) = ƩE(s^Xn | X1=j)P(X1=j) = Ʃs^j(E(s^Xn-1)P(X1=j) ?
Is there anywhere near correct? Where am I going wrong
generation of the separate branching processes spawned by these children, show that Fn(s),
defined by Fn(s) = E(s^Xn), satisfies
Fn(s) = F(Fn−1(s)) ∀n ≥ 2.
I need to prove the above result and have somewhat of an idea how to but I can't get the end result.
Here is my working thus far.
Fn(s) = E(s^Xn) = E(s^X1 + X2 +...+Xn) = E(s^j+X2+..+Xn) = s^j(E(s^Xn-1)
Then E(s^Xn | X1=j) = ƩE(s^Xn | X1=j)P(X1=j) = Ʃs^j(E(s^Xn-1)P(X1=j) ?
Is there anywhere near correct? Where am I going wrong